Pengaruh Peredaran Video Porno Terhadap Anak di Masyarakat (Tinjauan Kriminologi) - Wahab, Aris; Ramia, Machmud; Tangke, Elsa Nurida (HORIZON: Indonesian Journal of Multidisciplinary, 2023)
This study aims to determine the effect of the circulation of pornographic videos on children in society based on criminological reviews. This research uses a sociological juridical approach, namely discussions based on applicable laws and regulations and associated with legal theory and by looking at the reality that occurs in society. To collect the necessary data, library research techniques are used in analyzing the influence of the circulation of pornographic videos on children in the community and using a statutory approach (statute approach). This approach is to review laws and regulations related to the problems analyzed. Data obtained or successfully collected during the research process, both primary and secondary data, are analyzed qualitatively and then presented descriptively, namely explaining, describing, and describing in accordance with problems that are closely related to research. Based on the results of the study, it was found that the process of spreading pornographic videos in the community circulated along with the rapid development of technology. The majority of pornographic videos circulate through handtrees and are watched by children. The impact of the spread of pornographic videos on children is enormous. This causes damage to the child's morals and mindset